Correlating the five parameter grain boundary character distribution and the intergranular corrosion behaviour of a stainless steel using 3D orientation microscopy based on mechanical polishing serial sectioning. (1st September 2018) - An, D.; Griffiths, T.A.; Konijnenberg, P.; Mandal, S.; Wang, Z.; Zaefferer, S.
Abstract: Using 3D-orientation microscopy consisting of electron backscatter diffraction (EBSD) and serial sectioning by mechanical polishing we investigated the correlation between grain boundary (GB) character expressed by its 5-rotational parameters and the GB precipitation and intergranular corrosion (IC) behaviour on an AISI 304L stainless steel. From the measurements, a volume of approximately 4.8 × 10 6 μm 3 containing 451 grains and approximately 1500 GBs was reconstructed. Dominance of 111 planes for Σ3 n (n = 1, 2, 3) GBs was found. In general, the IC behaviour of random high angle grain boundaries (RHAGBs) and low-Σ coincidence site lattice (CSL) boundaries (Σ ≤ 29) does not show a large difference. The corrosion behaviour of low angle grain boundaries (LAGBs) is strongly dependent on the misorientation angles, while the crystallographic GB plane becomes dominant for the behaviour of low-Σ CSL GBs and RHAGBs. It was found that the corrosion resistance is related on the atom packing density (APD) of the GB plane. High corrosion resistance appears for GBs with high APD values (in particular for the (111) planes with a maximum APD value). Graphical abstract: Image 1